Variations in the Presence of Carotid Intraplaque Hemorrhage Across Age Categories: What Age Groups Are Most Likely to Benefit From Plaque Imaging? - Larson, Anthony S.; Benson, John C.; Brinjikji, Waleed; Savastano, Luis; Lanzino, Giuseppe; Huston, John; Nasr, Deena (Frontiers in Neurology, 2020)
Although carotid artery intraplaque hemorrhage (IPH) is a known risk-factor for cerebral ischemic events in patients of advanced age, its prevalence in younger cohorts is less certain. The purpose of this study was to assess the prevalence of carotid artery IPH across the age spectrum. A retrospective review was completed of all adult patients from our institution who underwent neck MRA with high-resolution carotid plaque imaging between 2017 and 2020. The mean ages of patients with and without IPH were calculated. The prevalence of IPH was compared between patients that were categorized into age groups. Patients with and without a cerebral ischemic event (e.g., stroke, retinal ischemia) were included. Unilateral anterior circulation ischemic events in patients without atrial fibrillation were presumed to be likely related to ipsilateral carotid artery disease. Multiple regression analysis was performed to determine independent associations with IPH. 634 patients were included (1,268 carotid arteries). Increasing age (OR: 1.04; 95% CI: 1.02–1.06; P = 0.001) was independently associated with IPH. 211 patients had unilateral anterior circulation ischemic events. The mean age of patients with carotid IPH was 71.4 years (SD = 9.9), compared to 62.8 years (SD = 15.8) of those without (P ≤ 0.0001). The prevalence of IPH increased with age in all patients (P = 0.0002). Among patients with ipsilateral anterior circulation ischemic events, each age category above 50 years had a significantly higher prevalence of IPH when compared to patients 18–50 years (P ≤ 0.05 for all comparisons). The prevalence of carotid IPH increases with age and is rare in patients under 50 years. The approximate threshold age for IPH development is likely around 50 years.